Suggestion of ergonomic evaluation index for agricultural ladders considering human-machine interaction - Mo, Seung-Min (Edelweiss Applied Science and Technology, 2025)
The purpose of this study is to suggest an ergonomic evaluation index, considering human-machine interaction, to ensure the fundamental safety of ergonomic equipment. To systematically investigate and analyze accident cases involving ladder-related injuries among agricultural workers, which is one of the most frequently used equipment in agricultural work, the ’Agricultural Safety 365’ database, operated by the Rural Development Administration of Republic of Korea, was utilized. This study conducted two focus group interviews (FGI) for consulting on the ergonomic evaluation index of agricultural ladders: one group consisting of agricultural safety experts and the other of agricultural workers. The causes of ladder-related accidents were classified into seven types, with most accidents occurring due to unstable floor conditions in agricultural work environments. As for the mechanical/equipment/tool related causes, accidents involving ladders (type A) were frequently found to occur due to the failure or absence of the device that secures the ladder’s extension. This study suggested the ergonomic evaluation index focusing on safety and usability indicators to consider human-machine interaction. The evaluation indices were derived using criteria such as accident probability, stability, effectiveness, and comfort, including factors like step anti-slip features, ease of ascension, anti-leg spreading devices, and the height/width between steps. Based on the results of this study, it can ensure fundamental safety from the design and production stages of ergonomic equipment and contribute to the creation of a safer agricultural work environment.